Qualimetric assessment of diets - Kuzmin, Oleg; Levkun, Kateryna; Riznyk, Anastasiia (My University, 2017)
The work’s objective is to analyze quality rating of diets from the standpoint of physiological need norms of a person and a daily ration, to further determine the balance of nutrition.
Keywords: кваліметрія; квалиметрия; qualimetry; раціон; рацион; rating; кафедра технології ресторанної і аюрведичної продукції